HISTOCHEMICAL CHANGES IN THE BRONCHOPULMONARY TRACT OF CATTLE NATURALLY INFESTED WITH HYDATIDOSIS. - J.Alwan , M. (The Iraqi Journal of Veterinary Medicine, 1992)
The object of this study was to demonstrate the histochemical changes in the mucosubstances of airways of cattle naturally infested with hydatid cysts for this purpose, 10 lungs infected with hydatid cysts were examind. The results showed that the granules of goblet cells and mucosal gland cell in the airways of hydatidosis cattle contain acid mucin mainly sialomucin as well as neutral mucin and sulphomucin with less degree.